(untitled) (Abhat Journal, 2023)
Teaching English as a foreign language is a profession with significant professional ethical standards. During the 21st century, EFL teachers’ adherence and commitment to ethical and professional standards are fundamental for succeeding in their careers. This study investigates 58 Libyan EFL university instructors’ awareness and commitment to these standards. The data was collected through an online close-ended questionnaire. The results indicate that Libyan universities have no written ethical codes of teaching practice and do not account for the instructor’s commitment to these codes. Nevertheless, the participants practiced some professional ethical behaviors according to their personal morals, values, and principles. There is a need for developing a consistent ethical code for the profession of teaching English as a foreign language in the Libyan context and maybe in other FL contexts.